2017
DOI: 10.1080/00918369.2017.1364944
|View full text |Cite
|
Sign up to set email alerts
|

Helping Young People Stay Afloat: A Qualitative Study of Community Resources and Supports for LGBTQ Adolescents in the United States and Canada

Abstract: LGBTQ youth are at increased risk of poor health outcomes. This qualitative study gathered data from LGBTQ adolescents regarding their communities and describes the resources they draw upon for support. We conducted 66 go-along interviews with diverse LGBTQ adolescents (mean age=16.6) in Minnesota, Massachusetts and British Columbia in 2014-2015, in which interviewers accompanied participants in their communities to better understand those contexts. Their responses were systematically organized and coded for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Prior research has indicated that greater rurality is associated with greater exposure to hostile school contexts (Kosciw et al., ), which is somewhat consistent with the More Desired Than Received group pattern. GSAs can also serve as a facilitator of connections to other resources for students (Eisenberg et al., ; Porta et al., ); in settings with few resources (e.g., suburban or rural areas with few LGBT‐specific agencies or social settings), this may not be so helpful. However, in resource‐rich settings, such as may be the case in some cities, this networking capacity of GSAs can be of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has indicated that greater rurality is associated with greater exposure to hostile school contexts (Kosciw et al., ), which is somewhat consistent with the More Desired Than Received group pattern. GSAs can also serve as a facilitator of connections to other resources for students (Eisenberg et al., ; Porta et al., ); in settings with few resources (e.g., suburban or rural areas with few LGBT‐specific agencies or social settings), this may not be so helpful. However, in resource‐rich settings, such as may be the case in some cities, this networking capacity of GSAs can be of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Community climate refers to the sum of the messages and supports LGBTQ people receive from various community sources (Oswald et al 2010). These messages and supports may be formal (e.g., anti-discrimination policies, LGBTQinclusive organizations) or more informal (e.g., emanating from interpersonal interactions, visual cues including rainbows, LGBTQ-inclusive coffee shops; Eisenberg et al 2018;Oswald et al 2010;Wolowic et al 2017). Communities vary widely on the amount of formal and informal LGBTQsupportive resources they provide (Eisenberg et al 2018).…”
Section: Supportive Community Climate and Lgbq Youth Bullying Victimimentioning
confidence: 99%
“…Victimization based on stigma severely jeopardizes the psychosocial development and overall health of LGBTQ+ students [15,16,17,18]. It poses a serious threat to these students' mental health, and its negative effects are witnessed in their academic performance and overall well-being [19,20,21]. High levels of victimization for LGBTQ+ students are linked to reduced self-esteem, few plans for postsecondary education, increased substance abuse, high suicide risks, and increased incidences of depression [22].…”
Section: Bullying and Victimizationmentioning
confidence: 99%